English Learners in California Schools: Unequal resources, 'Unequal outcomes - Patricia Gándara; Russell Rumberger; Julie Maxwell-Jolly; Rebecca Callahan (Arizona State University, 2003)
The Williams vs the State of California class action suit on behalf of poor children in that state argues that California provides a fundamentally inequitable education to students based on wealth and language status. This article, an earlier version of which was prepared as background to that case, reviews the conditions of schooling for English learners in the state with the largest population of such students, totaling nearly 1.6 million in 2003, and comprising about 40 percent of nation's English learners. We argue, with evidence, that there are seven aspects of the schooling of English language learners where students receive an education that is demonstrably inferior to that of English speakers. For example, these students are assigned to less qualified teachers, are provided with inferior curriculum and less time to cover it, are housed in inferior facilities where they are often segregated from English speaking peers, and are assessed by invalid instruments that provide little, if any, information about their actual achievement. We end with suggestions for ways in which teachers, administrators, and policymakers can begin to address these inequities, even while legal remedies may remain in the distant future.